1996
DOI: 10.1101/gr.6.6.465
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transcription map of the murine bare patches (Bpa) and striated (Str) critical regions and human Xq28.

Abstract: The X-linked developmental mouse mutations bare patches (Bpa) and striated {Str) may be homologous to human X-linked dominant chondrodysplasia punctata (CDPX2) and incontinentia pigmenti (IP2), respectively, based on their genetic mapping and clinical phenotypes. Bpa and Str have been localized to an overlapping critical region of 600 kb that demonstrates conserved gene order with loci in human Xq28 between DXSII04 and DXS52. As part of efforts to isolate the genes involved in these disorders, we have begun to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The organization of the three GABR genes (⑀-␣3-) on the human X chromosome (Fig. 3E), plus their same order found on the mouse X chromosome (35,39), when compared with the other clusters would be consistent with ⑀ being derived from the ␥ line and from the ␤ line of GABR genes of an ancestral chordate. However, species specialization within the ␥3 subgroup might have occurred independently.…”
Section: Locations and Clusters Of All Gaba A Receptor Genesmentioning
confidence: 63%
See 1 more Smart Citation
“…The organization of the three GABR genes (⑀-␣3-) on the human X chromosome (Fig. 3E), plus their same order found on the mouse X chromosome (35,39), when compared with the other clusters would be consistent with ⑀ being derived from the ␥ line and from the ␤ line of GABR genes of an ancestral chordate. However, species specialization within the ␥3 subgroup might have occurred independently.…”
Section: Locations and Clusters Of All Gaba A Receptor Genesmentioning
confidence: 63%
“…That band location is as found for GABRE (33), for ␣3 (10, 11), and for (34,35). We have derived the precise locations, separations, and sizes of the genes there (Fig.…”
Section: Locations and Clusters Of All Gaba A Receptor Genesmentioning
confidence: 99%
“…The critical region containing these two mutations is flanked by the loci DXHXS1104 and DXHXS52 (Levin et al 1996). In addition, we have completed the sequencing of the homologous human region.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have completed the sequencing of the homologous human region. In the mouse, cosmid contigs partially spanning the Bpa/Str critical region were already available (Chatterjee et al 1994;Levin et al 1996) and STS markers and previously identified genes were used to construct a BAC and PAC contig (see Methods). Thirteen markers were used to isolate clones and facilitate contig construction, resulting in 28 clones selected for further characterization.…”
Section: Resultsmentioning
confidence: 99%
“…The quality and concentration of RNA samples were assayed using an Agilent 2100 Bioanalyzer (Agilent Technologies, Palo Alto, CA). RT-PCR and DNA sequencing of cDNA to test for the monoallelic expression of Nsdhl in sorted cell populations were performed as described (21) using a forward primer from exon 2 (NsdhlE2F, 5 Ј -CCAGCTGAT-CATGGTGAATC-3 Ј ) and a reverse primer from exon 5 (NsdhlE5R, 5 Ј -TGGCACTGCTGGTTAAAATGAGTTT-3 Ј ), generating a 400 bp PCR product that spans the site of the Bpa 1H mutation in exon 4.…”
Section: Rt-pcr Sequencing and Microarraysmentioning
confidence: 99%